Military religion in Roman Britain - Irby-Massie, Georgia L. 1965- (Mnemosyne, Supplements, 1999)
This volume deals with the religions of the Roman soldiers in Britain and the religious interactions of soldiers and civilians. Drawing on epigraphic and archaeological evidence, the discussion shows the complexities of Roman, Eastern, and Celtic rites, how each system influenced the ritual and liturgy of the others, and how each system was altered over time. The first part presents discursive chapters on topics such as the cult of the emperor, Mithraism in Britain, the cults of Celtic warriors and healers, the Romanization of Civilian religions, and Christianity; the second part consists of an annotated catalogue of the epigraphical sources. Of significance is the broad range of materials synthesized to show the extent to which native religions influenced and were influenced by imported Roman and Eastern cults.